2013
DOI: 10.1063/1.4802484
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the anomalous Hall effect in Ni thin films by artificial interface modification

Abstract: The enhancement of the anomalous Hall effect has been realized by capping one monolayer Cu on Ni thin films. This approach with artificial interface engineering is proved to be an effective way to improve spin to charge transformation and may have potential application in spintronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…This is the so-called TYJ scaling, [27] which has been used to successfully distinguish these three contributions in many systems. [34][35][36][37][38][39] In the equation,…”
Section: Separation Of Intrinsic and Extrinsic Mechanisms Via Applicamentioning
confidence: 99%
“…This is the so-called TYJ scaling, [27] which has been used to successfully distinguish these three contributions in many systems. [34][35][36][37][38][39] In the equation,…”
Section: Separation Of Intrinsic and Extrinsic Mechanisms Via Applicamentioning
confidence: 99%
“…The saturation magnetization of the samples could be estimated by the magnetic saturation field in Hall resistivity curves, since the samples have in-plane magnetization (demagnetization factor N = 1 in out-of-plane direction), as shown in Fig. 3 Since we observed the variation of anomalous Hall resistivity for these samples with different seed layers, one may quest if the variation is caused by the interfacial spin-orbital coupling [25,26] or interfacial modification [27] other than the surface roughness. We then prepared several samples with the same roughness but different interfacial spin-orbital coupling.…”
Section: Anomalous Hall Effect Scaling Analysis 233mentioning
confidence: 92%
“…13 Jin et al showed an enhancement of anomalous Hall effect (AHE) by interfacial modification. 14 Our recent work shows anomalous Hall effect can be greatly enhanced by inserting an ultrathin CoO layers at MgO/[Co/Pt] 3 bottom and [Co/Pt] 3 /MgO top interfaces. 15 In this paper, the interfacial structures were characterized by Xray photoelectron spectroscopy (XPS), showing that the MgO/Co interface and Co/MgO interface including chemical states play a dominant role on spin-dependent transport, leading to different anomalous Hall behavior.…”
mentioning
confidence: 93%